THE ROLE OF HARDINESS PERSONALITY ON WORKLIFE BALANCE WITH INTERNAL LOCUS OF CONTROL AS A MEDIATION VARIABLE - Endang Sapti Prihatini; Suryani Hardjo; Yudistira Fauzy Indrawan (RADJA PUBLIKA, 2025)
Complex challenges force professional workers, especially female police officers, to maintain a balance between their professional and personal lives. Their duties are not only physically demanding but also emotionally and psychologically demanding. This can lead to an imbalance between their personal and work lives (work-life balance) that can potentially reduce their well-being and performance. This study aims to analyze the effect of hardiness personality on work-life balance, with locus of control as a mediating variable. The implications of this study emphasize the importance of institutional support in enhancing psychological resilience and stress management strategies for female police officers to improve their well-being and work effectiveness. A quantitative explanatory approach with Structural Equation Modeling (SEM) was used to analyze the relationship between variables. The study sample consisted of 163 female police officers in the Aceh Regional Police selected through purposive sampling. Data collection was conducted using the hardiness personality scale, work-life balance scale, and locus of control scale. Hypothesis testing on hardiness personality shows a p value of 0.000 (p <0.05), a p value of 0.000 (p <0.05) on work-life balance, a p value of 0.024 (p <0.05) on LoC, and a p value of 0.038 (p <0.05) on Loc as a mediator. Based on these results, it can be concluded that hardiness personality can influence work-life balance through Locus of Control.